SHM_121006_HST_3D Three-Legged Ceramic Pot with Handle - Bonnevier, Helena; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a three-legged ceramic pot with handle from the Middle Ages, collected in the field at Slottsfjärden in Kalmar and currently in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=664

Link to Sök I Samlingarna

https://samlingar.shm.se/object/C8384449-BCD9-49D8-8A61-0E25133EC0B7
Keywords: Museum Object; 3D Model; Archaeology; Archaeology; Photogrammetry; Archaeology/history; History and archaeology; Dynamic Collections; Swedish Middle Ages; Slottsfjärden; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi